STUDENTS' PERCEPTIONS TOWARD THE DOMINANT USE OF ENGLISH AS A MEDIUM OF INSTRUCTION AT A UNIVERSITY IN JAMBI - Oktavia, Eka Rizki; Wulandiri, Bunga Ayu; Abrar, Mukhlash; Heryanti, Reny (Magister Pendidikan Bahasa Inggris Universitas Jambi, 2022)
The purposes of this qualitative research were to know what the students perceive, difficulties and students' strategies to overcome challenges listening to lecturers who use mainly English as a medium of instruction. In doing this research, the researcher used a basic interpretive approach. There were 10 participants participated in this research. Data collection techniques are by using interviews. The results of the research showed that the researcher found there is some student who agrees with using English and agree with the terms and condition. The result also indicated that two themes of difficulties were identified, including internal (lack of vocabulary and lack of knowledge) and external (lecturer accents, and lecturer's attitude). This result also revealed that there were three identified studentsâ€™ strategies to overcome challenges listening to lecturers who mainly use English as a medium of instruction, including self-management (practice, reading the material before learning, less noise or distraction), asking for help (asking friends and asking lecturer),Â and the benefits of technology (listening to music, opening google translate, and opening dictionary) Â Keywords: Student, perceptions, Dominant, English, University